2013
DOI: 10.5999/aps.2013.40.5.492
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Lesion? Glomus Tumours of the Hand

Abstract: Glomus tumours are vascular hamartomas that are commonly found in the hand, particularly the subungual region. They appear as solitary or multiple tumours, and often present as a bluish discoloration of the nail plate. Different diagnostic tests are outlined, as well as imaging studies such as magnetic resonance imaging and ultrasound. Misdiagnosis and delayed diagnosis of these tumours are common, while a familial tendency is a potential risk factor but not yet proven. Complete surgical excision often results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…18 In a study conducted by Netscher et al, 17 it was found that the Cold sensitivity test had 100% sensitivity, specificity, and accuracy. The Love's pin test was found to be 100% sensitive with 78% accuracy.…”
mentioning
confidence: 99%
“…18 In a study conducted by Netscher et al, 17 it was found that the Cold sensitivity test had 100% sensitivity, specificity, and accuracy. The Love's pin test was found to be 100% sensitive with 78% accuracy.…”
mentioning
confidence: 99%
“…In addition, there is reported to be up to a 10% recurrence rate, thought to be due to incomplete excision 3. The ability to provide a complete excision can get complicated if undertaking an initial diagnostic punch biopsy, as the glomus tumour can occasionally have poorly defined margins leaving residual tumour to regrow, facilitating the requirement for further surgery 5 6…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Typically, they occur as encapsulated solitary lesions. Up to 75% of the tumors occur in the hand, mainly on the subungual area of the fingertips.…”
mentioning
confidence: 99%
“…2 Surgical excision of the tumor is recommended and considered a curative treatment. As the tumor increases in size, it may induce nail deformity or phalangeal bone indentation.…”
mentioning
confidence: 99%